Baseline investigations of folate status in Aboriginal and non-Aboriginal West Australians prior to the introduction of mandatory fortification - Maxwell, S.; Brameld, Kate; Bower, C.; D'antoine, H.; Hickling, S.; Marley, J.; O'Leary, Peter (Wiley-Blackwell Publishing Asia, 2013)
Objective: In September 2009, Australia implemented mandatory folic acid fortification of wheat flour for bread-making to reduce the incidence of neural tube defects. Our study aimed to establish baseline folate status data in Aboriginal and non-Aboriginal Western Australians. Methods: Patients who presented at a health service or collection centre for blood tests were invited to participate. One hundred and ninety-one Aboriginals and 159 non-Aboriginals were recruited between April 2008 and September 2009. Participants completed a five-minute questionnaire and had blood taken for red blood cell (RBC) folate and serum vitamin B12. Data were analysed using SPSS (version 17.0.2, SPSS Inc., Chicago, IL, USA).Results: Ten per cent (95% confidence intervals (CI): 5, 19) of the Aboriginal women participants and 26% (95% CI:16, 40) of men had RBC folate concentrations below 250 ng/mL, the cut-off associated with folate deficiency. None of the non-Aboriginal women (95% CI: 0, 4) and 4% of the non-Aboriginal men (95% CI: 2, 12) had RBC folate concentrations below 250 ng/mL. All participants were vitamin B12 replete. None of the 96 Aboriginal and 8% of non- Aboriginal women aged 16–44 reported consumption of supplements with a daily intake of >400 µg folic acid during the previous week. Conclusions and implications: This study established a baseline of RBC folate, folate consumption and supplement use in Aboriginal and non-Aboriginal groups. We identified 10% of Aboriginal women and none of non-Aboriginal women participants with low folate concentrations. The higher prevalence of folate deficiency in Aboriginal participants suggests they are more likely to benefit from a universal program of folate fortification.